A Systematic Evaluation of Environmental Discrimination with Sustainability Initiatives in India - Williams, Jonah (Consilience, 2016)
In the past fifty-years, India has undeniably become one of the world’s economic and industrial superpowers, dominating the geopolticial climate of South Asia. India’s road to industrialization has been accompanied by extreme environmental devastation which is encapsulated by population growth, pollution, and loss of biodiversity; additionally, many of these factors have had crippling effects on certain areas of India’s environment. To combat these problems, certain groups within the government and nation, such as the Ministry of New and Renewable Energy, have been implementing sustainable solutions to combat the adverse effects of man-made environmental degradation. Oftentimes however, the implementation of these conservation tactics is done at a state-wide or national level in what is masked as “soft-authoritarianism” and fail to consider the interests and accessibility of programs for all peoples; especially communities which are labeled as minority, indigenous, slum, or lower caste (Dalit) leading to the rise of environmental prejudices. Although India has come a long way in the past decade regarding action against environmental problems through new sustainable solutions, it has failed to consider the accessibility of these programs to all peoples and the alleviation of environmental discrimination. This paper considers the convoluted nature of the past and aims to propose solutions that will a) allow India to continue its commitment to a sustainable future and b) combat socio-political issues of environmental biases, which adhere to the paradigm of Community-Based Natural Resource Management (CBNRM).